If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2x + 4)(5x + -6) = 0 Reorder the terms: (4 + -2x)(5x + -6) = 0 Reorder the terms: (4 + -2x)(-6 + 5x) = 0 Multiply (4 + -2x) * (-6 + 5x) (4(-6 + 5x) + -2x * (-6 + 5x)) = 0 ((-6 * 4 + 5x * 4) + -2x * (-6 + 5x)) = 0 ((-24 + 20x) + -2x * (-6 + 5x)) = 0 (-24 + 20x + (-6 * -2x + 5x * -2x)) = 0 (-24 + 20x + (12x + -10x2)) = 0 Combine like terms: 20x + 12x = 32x (-24 + 32x + -10x2) = 0 Solving -24 + 32x + -10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-12 + 16x + -5x2) = 0 Factor a trinomial. 2((-2 + x)(6 + -5x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Subproblem 2
Set the factor '(6 + -5x)' equal to zero and attempt to solve: Simplifying 6 + -5x = 0 Solving 6 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Divide each side by '-5'. x = 1.2 Simplifying x = 1.2Solution
x = {2, 1.2}
| (3m^-3/2n^-2)^-3 | | 6x^3-33x^2+45x=0 | | (7-2)p=5-8 | | 1/3g+4=2 | | 2/7p+8=1/2p+5 | | 23=9+7x | | 3x+53=8-2x | | 5x+3-4x=-7 | | xsquared+px-q=0 | | 25c=2c-9 | | 9+x+5=44-x | | 24/36=2/x | | 10b+7= | | 3y-x=180 | | 5x+12-3x=8x+3 | | 2y+x=90 | | d/dx=x^3 | | d/dxx^2/3 | | 9x-2=6+8x | | (4x+5)^4/5=81 | | 60=-2x-2x+6(x+10) | | 42=7+z/5 | | -64=-4(n-5) | | 2(x+5)+3(x-10)=100 | | 2x-4(x+3)-10=6 | | -(2x+8)=-20 | | x-7=.5x | | -6(n+4)=30 | | 5b+12-2b+6=-15 | | 520=6x+3x+x | | y=3x^2-18x-27 | | 49=10+P/5 |